A Test of Two Spatial Frameworks for Representing Spatial Patterns of Wetness in a Glacial Drift Watershed. Issue 1 (1st February 2019) - Hofmeister, K.L.; Nave, L.E.; Riha, S.J.; Schneider, R.L.; Walter, M.T.
Abstract : Core Ideas: Soil moisture and water table position vary across ecosystems and parent materials. Ecosystem classifications and topographic wetness indices represent moisture status. Topographic wetness indices perform best in till rather than outwash soils. Including soil properties with topographic information improves moisture estimates. In forest ecosystems, soil water availability is an important indicator and driver of biogeochemical transformations, pedogenesis, and surface water–groundwater linkages. Given the importance of soil moisture and shallow groundwater to ecosystem processes, field measurements are critical. We investigated the spatial patterns and temporal dynamics of moisture conditions in a forested first‐order watershed in northern Michigan. We measured soil volumetric water content (VWC, %) and water table levels across a range of glacial parent materials and landforms. We also assessed the utility of using two different spatial frameworks (Landscape Ecosystem classification, Topographic Wetness Index) to represent spatial patterns of soil moisture and water table levels across the watershed. At the lowest landscape position (outwash‐lake plain swamp), saturation was perennial, with a median soil VWC of 53% and the water table 8 cm below ground surface. Among upland ecosystems, outwash landforms had consistently low VWC (16%) and showed no evidence of groundwater within 4 m of the surface; moraine ecosystems (till parent material) possessed mixed hydrologic conditions, with VWC ranging from 18 to 25% and water table levels 6 to 65 cm below the surface. In low‐variability dry or wet areas with relatively homogenous soils, larger ecosystem classification map units provide good representations of moisture conditions. In the more heterogeneous till soils, a finer‐scale spatial framework that accounts for local soil variation is optimal. A combination of both spatial frameworks is most appropriate for estimating moisture conditions in this glaciated landscape and can be used to identify biogeochemically important sites and to inform land management decisions.